Novel Lipid Long Intervening Noncoding RNA, Oligodendrocyte Maturation‐Associated Long Intergenic Noncoding RNA, Regulates the Liver Steatosis Gene Stearoyl‐Coenzyme A Desaturase As an Enhancer RNA. Issue 10 (14th August 2019) - Benhammou, Jihane N.; Ko, Arthur; Alvarez, Marcus; Kaikkonen, Minna U.; Rankin, Carl; Garske, Kristina M.; Padua, David; Bhagat, Yash; Kaminska, Dorota; Kärjä, Vesa; Pihlajamäki, Jussi; Pisegna, Joseph R.; et al.
Abstract : The global obesity epidemic is driving the concomitant rise in nonalcoholic fatty liver disease (NAFLD). To identify new genes involved in central liver functions, we examined liver RNA‐sequence data from 259 patients who underwent morbidly obese bariatric surgery. Of these patients, 84 had normal liver histology, 40 simple steatosis, 43 nonalcoholic steatohepatitis, and the remaining 92 patients had varying degrees of NAFLD based on liver histology. We discovered oligodendrocyte maturation‐associated long intergenic noncoding RNA ( OLMALINC ), a long intervening noncoding RNA (lincRNA) in a human liver co‐expression network (n = 75 genes) that was strongly associated with statin use and serum triglycerides (TGs). OLMALINC liver expression was highly correlated with the expression of known cholesterol biosynthesis genes and stearoyl‐coenzyme A desaturase ( SCD ). SCD is the rate‐limiting enzyme in monounsaturated fatty acids and a key TG gene that is known to be up‐regulated in liver steatosis and NAFLD and resides adjacent to OLMALINC on the human chromosome 10q24.31. Next, we functionally demonstrated that OLMALINC regulates SCD as an enhancer‐RNA (eRNA), thus describing the first lincRNA that functions as an eRNA to regulate lipid metabolism. Specifically, we show that OLMALINC promotes liver expression of SCD in cis through regional chromosomal DNA–DNA looping interactions. Conclusion: The primate‐specific lincRNA OLMALINC is a novel epigenetic regulator of the key TG and NAFLD gene SCD .